REPRESENTATION OF HOBBESIAN THEORY IN THE FILM SERIES â€œSQUID GAMEâ€ IN THE VIEW OF GENERATION Z - Adryan Allen Gerald Witera; Albert Louis; Jovita Anggi Taruli; Nurmalita Sari (Jurnal Kewarganegaraan, 2021)
Abstract‘Squid Game’ is a film series from South Korea that is in high demand lately. This film tells the story of a group of people who are in debt and end up participating in a game competition that puts their lives on the line to earn money. This game is designed by a frontman who manages to avoid chaos during the game. Each player has also signed an agreement/contract while at the game venue. In this paper, we will discuss the representation of the running of politics and government within the scope of the country from the film series ‘Squid Game’ based on the social-political theory of Thomas Hobbes. This research was conducted by means of literature studies and surveys. Based on the results of data analysis, there are things in this film that can describe the politics and government of the country. Frontman describes the position of a leader of a country, players describe the position of citizens, game contracts describe the laws of the country that must be obeyed, and the game place describes the territory of a country. This film also describes social conflicts that may occur among the people, proletarian rebellions, and the government's way of dealing with conflicts with dictatorial systems, democracy, and others. From the research results, readers can see this film from a different perspective and can better understand the world of politics and state government.Keywords: 'Squid Game', politic, country, government, Hobbesian AbstrakSquid Game adalah serial film dari Korea Selatan yang sangat diminati akhir-akhir ini. Film ini bercerita tentang sekelompok orang yang berhutang dan akhirnya berpartisipasi dalam kompetisi game yang mempertaruhkan nyawa mereka untuk mendapatkan uang. Game ini dirancang oleh frontman yang berhasil menghindari kekacauan selama pertandingan. Setiap pemain juga telah menandatangani perjanjian/kontrak saat berada di tempat permainan. Dalam makalah ini, kita akan membahas representasi jalannya politik dan pemerintahan dalam lingkup negara dari seri film 'Squid Game' berdasarkan teori sosial-politik Thomas Hobbes. Penelitian ini dilakukan melalui studi literatur dan survei. Berdasarkan hasil analisis data, ada hal-hal dalam film ini yang bisa menggambarkan politik dan pemerintahan negara. Frontman menggambarkan posisi seorang pemimpin suatu negara, pemain menggambarkan posisi warga negara, kontrak permainan menggambarkan hukum negara yang harus dipatuhi, dan tempat permainan menggambarkan wilayah suatu negara. Film ini juga menggambarkan konflik sosial yang mungkin terjadi di antara rakyat, pemberontakan proletar, dan cara pemerintah menangani konflik dengan sistem diktator, demokrasi, dan lain-lain. Dari hasil penelitian, pembaca dapat melihat film ini dari perspektif yang berbeda dan dapat lebih memahami dunia politik dan pemerintahan negara bagian.Kata kunci: 'Squid Game', politik, negara, pemerintah, Hobbesian